The Role and Mechanism of AMPK Pathway Activation by NUDT1 in Oral Squamous Cell Carcinoma - Haobing Guo; Changsheng Sun; Lili Lu; Bowen Zhao; Yacui Hao; Yihan Gao; Songlin piao (Current Molecular Medicine, 2026)
Introduction: This research aimed to investigate the effects of Nudix Hydrolase 1 (NUDT1) on Oral Squamous Cell Carcinoma (OSCC) cells, along with its relationship with the AMP-activated Protein Kinase (AMPK) signaling pathway. Methods: Immunohistochemical methods, Western blotting, and quantitative real-time polymerase chain reaction (qRT-PCR) were used to assess the levels of NUDT1 expression in these OSCC tissues and normal tissues. The prognosis of all patients was followed up. The Kaplan‒Meier method was used to analyze the survival rate. Scratch, CCK8, and apoptosis assays were used to analyze the impact of NUDT1 downregulation on cell migration, proliferation, and apoptosis. Western blotting was used to assess AMPK activation after the downregulation of NUDT1. Results and Discussion: NUDT1 expression was substantially elevated in OSCC tissues and strongly correlated with pathological grade and tumor stage. All patients with high NUDT1 expression had lower Overall Survival (OS) (P = 0.0259) and Disease-Specific Survival (DSS) (P = 0.0129) rates than patients with low NUDT1 expression (P ＜ 0.05). In addition, the expression of NUDT1 was also greater in both CAL27 and HN30 OSCC cells than in normal cells. Downregulation of NUDT1 expression inhibits the migration and proliferation of Oral Squamous Cell Carcinoma (OSCC) cells and promotes their apoptosis. Furthermore, inhibition of NUDT1 also increased p-AMPK expression. Conclusion: This investigation thoroughly revealed the significance of NUDT1 in OSCC. NUDT1 plays an important role in the proliferation, migration, and apoptosis of OSCC cells and affects the AMPK signaling pathway.